2016
DOI: 10.3892/ol.2016.4908
|View full text |Cite
|
Sign up to set email alerts
|

4-HPR impairs bladder cancer cell migration and invasion by interfering with the Wnt5a/JNK and Wnt5a/MMP-2 signaling pathways

Abstract: In order to identify the anti-invasive and anti-metastatic effect of the synthetic retinoid N-(4-hydroxyphenyl) retinamide (4-HPR) on the human bladder cancer EJ cell line, and to study its impact on the expression of wingless-type mouse mammary tumor virus integration site family, member 5a (Wnt5a), the phosphorylation of c-Jun N-terminal kinase (JNK), the expression levels of matrix metalloproteinase-2 (MMP-2), and the migration and invasion of EJ cells, migration and Matrigel invasion assays, as well as wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…There are no other sources of information on the MMP2 regulation by WNT5A in arthritis, but in cancer cells the two types of results can be found. Several cells show induction of MMP2 by WNT5A (55,56), but others show inhibition (57). The cancer studies are also of interest because they show that WNT5A stimulates MMP2 expression through ROR2 (55,56), a receptor that was expressed at low levels in the RA FLS and that was not involved in the WNT5A modulation of migration suggesting a possible mechanism of the differential MMP2 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…There are no other sources of information on the MMP2 regulation by WNT5A in arthritis, but in cancer cells the two types of results can be found. Several cells show induction of MMP2 by WNT5A (55,56), but others show inhibition (57). The cancer studies are also of interest because they show that WNT5A stimulates MMP2 expression through ROR2 (55,56), a receptor that was expressed at low levels in the RA FLS and that was not involved in the WNT5A modulation of migration suggesting a possible mechanism of the differential MMP2 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and MMP-9 play a significant role in promoting the invasion and migration of gastric cancer cells, whereas TIMP-1 inhibits this process by regulating MMP-9. 2732 This study showed that inhibition of Vav2 in BGC823 cells leads to markedly reduced expression of MMP-2 and MMP-9 and significantly increased expression of TIMP-1, suggesting that Vav2 gene in gastric cancer cells may be involved in invasion and metastasis of gastric cancer cells by regulating MMP-2, MMP-9, and TIMP-1. However, the molecular mechanism needs further study.…”
Section: Discussionmentioning
confidence: 79%
“…MMP-2 and MMP-9 play a significant role in promoting the invasion and migration of gastric cancer cells, whereas TIMP-1 inhibits this process by regulating MMP-9. [27][28][29][30][31][32] This study showed that inhibition of Vav2 in Table 2. Expression of Rac1, MMP-2, MMP-9, and TIMP-1 proteins in gastric cancer and normal gastric mucosa (n = 115).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WNT5a is one of the most statistically significant upregulated genes as a result of SOX4 knockdown and significantly downregulated upon the re-expression of SOX4. WNT5a expression has been shown to decrease the migratory or invasive characteristics in FTC-133 thyroid cell lines and EJ bladder cancer cell lines (53,54), a derivative of T24 cells. In this study, we confirmed the high expression of WNT5a in T24-SOX4-KD cell lines compared to the T24-Scr and T24-SOX4-Rescue cell lines by RT-qPCR (Fig.…”
Section: Resultsmentioning
confidence: 99%